Impact of potassium fertilizers with different active ingredients and dosages on potato yield in experiments in the Nyírség region - Kruppa, J.; Zsom, E. (International Journal of Horticultural Science, 2006)
A five-year experiment was carried out in the Nyírség on its characteristic soil type, brown forest soil to investigate the impact of three types of potassium fertilizers (potassium chloride, potassium sulfate and Patentkali) in three different dosages (80, 160, 240 kg/ha K20), under non-irrigated conditions applying the same dosages of N, P in all treatments (the applied amount was different between years) in 10 treatments including the control on 50 m2-parcels with 3 or 4 replicates. The test plant was cultivar Desiree, Kondor, Agria and Pannonia in 1998 and 2000, 2001, 2002 and 2003, respectively. The obtained yields were analyzed by an analysis of variance. Based on the five-year results, the highest yields on the acidic sandy and sandy loam soils were obtained in the treatments with 530-800 kg/ha Patentkali containing 30% of K and 10% of magnesium active ingredients in addition to the same amounts of N and P applications. The dosage of 530 kg/ha Patentkali contains 160 kg/ha K+ 53 kg/ha Mg active ingredients, while the dosage of 800 kg/ha Patentkali contains 240 kg/ha K+ 80 kg/ha Mg active ingredients. It can be concluded that the potassium chloride fertilizer (KCI) was the least effective as regards yields and Patentkali proved to be the most effective fertilizer, it had higher yields than even those of potassium sulfate, the difference in the 160 kg/ha treatments was 17.7%, which was a significant difference. Based on the results of the multi-year experiment, we recommend to apply 530 kg/ha Patentkali fertilizer (160 kg/ha K+ 53 kg/ha Mg active ingredients) for the fertilization in potato under non-irrigated conditions on the acidic sandy and sandy loam forest soils of the Nyírség, which proved to be the most effective treatment and with which we could obtain 30 t/ha yield in the average of the years (with the simultaneous application of N and P).